LIGHT INTENSITY STUDY IN SYEKH YUSUF GENERAL HOSPITAL, GOWA DISTRICT, SOUTH SULAWESI PROVINCE - Gunawan Zain, Satria; Ripaldi, Ripaldi (Journal of Electrical Engineering and Informatics, 2025)
Lighting plays a crucial role in hospital environments, directly impacting the efficiency of medical staff and the comfort of patients. This study aims to analyze the light intensity in various rooms of Syekh Yusuf General Hospital, Gowa District, South Sulawesi Province, and evaluate its compliance with the Indonesian Ministry of Health Regulation No. 24 of 2016. A descriptive quantitative approach was employed, with data collected through observations, direct measurements using a lux meter, and documentation. Measurements were conducted in 51 rooms, including inpatient rooms, delivery rooms, laboratories, emergency rooms, polyclinics, and the lobby. The results indicate that 46 rooms (90%) meet the required lighting standards, while five rooms do not due to factors such as dim or unclean light fixtures and poorly maintained luminaires. The findings align with previous studies emphasizing the importance of optimal lighting in healthcare settings to reduce eye strain, enhance productivity, and improve patient recovery. The study highlights the need for regular evaluations and a structured maintenance program to ensure consistent lighting quality. Implementing automated lighting systems and tailored illumination for specific hospital functions is recommended to enhance both medical efficiency and patient well-being.